Nut consumption in chronic kidney disease: a systematic review - Lazzarin, Taline; Ballarin, Raquel SimÃµes; Azevedo, Paula Schmidt; Cardoso, Barbara R.; Minicucci, Marcos Ferreira (Frontiers in Nutrition, 2025)
IntroductionNuts possess a beneficial nutritional profile with antioxidant and anti-inflammatory properties, potentially improving health outcomes in chronic kidney disease (CKD) patients. This systematic review evaluates the association between nut intake and lipid profile, inflammation, oxidative stress, blood pressure, and mortality in patients with CKD.MethodsA systematic search was performed in Medline, EMBASE, Scopus, CINAHL, and Cochrane Library databases on 27 May 2024 and repeated on 13 February 2025 without restrictions on date, language, or study type.ResultsThe search identified 2,521 records, with four studies (three trials, one cohort) involving 1,270 CKD patients meeting the inclusion criteria. The studies were heterogeneous in terms of intervention and biomarkers assessed, and all of them had moderate-to-high risk of bias. Overall the findings indicate positive effects of Brazil nuts and baru almond oil on oxidative stress and inflammation markers, while walnuts reduced LDL cholesterol and blood pressure while posing no risk regarding electrolytes balance. Further, the consumption of total nuts was associated with reduction in all-cause mortality.ConclusionOur review indicates potential benefits for the inclusion of nuts in the diet of patients with CKD, but further studies are required to translate findings into practice.Systematic review registrationPROSPERO, Registration no CRD42024543880. https://www.crd.york.ac.uk/PROSPERO/view/CRD42024543880.